2015
DOI: 10.5539/ijbm.v10n7p158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Demography, Religiosity and Porting Behaviour on Switching Behaviour of Mobile Subscribers: Evidence from A Developing Country

Abstract: The paper examines the extent to which consumer demography, religiosity and porting behaviour predict consumer switching behaviour (CSB) in the context of mobile subscribers from an emerging market perspective. Drawing from relevant literature, a predictive model was developed to test the influence of demography, religiosity and porting behaviour on CSB. Empirical data were collected through a cross-sectional survey design involving 736 mobile subscribers from six telecoms in Ghana. Data were analysed using bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…family and friends, co-workers and existing banking consumers, financial advisors, financial regulators and consumer protection agencies) who tend to influence consumers' decisions towards banking products/services (Milakovi c et al, 2020;Yen et al, 2019;Cucinelli et al, 2016). In Ghana, Nimako and Nyame (2015) reported that unsatisfied consumers were likely to warn family and friends from using the services of their banks. Hedonically, emotional pleasure and arousal are strongly and positively linked to consumer readiness to engage in word-ofmouth (WoM) recommendations (Gulfraz et al, 2022).…”
Section: Subjective Norm (Sn) and Consumer Pre-banking Intentionsmentioning
confidence: 99%
“…family and friends, co-workers and existing banking consumers, financial advisors, financial regulators and consumer protection agencies) who tend to influence consumers' decisions towards banking products/services (Milakovi c et al, 2020;Yen et al, 2019;Cucinelli et al, 2016). In Ghana, Nimako and Nyame (2015) reported that unsatisfied consumers were likely to warn family and friends from using the services of their banks. Hedonically, emotional pleasure and arousal are strongly and positively linked to consumer readiness to engage in word-ofmouth (WoM) recommendations (Gulfraz et al, 2022).…”
Section: Subjective Norm (Sn) and Consumer Pre-banking Intentionsmentioning
confidence: 99%
“…The study was conducted with the objective of building a conceptual model on the basis of various empirical studies done in the past. Nimako and Nyame (2015) empirically examined validated theoretical models to explain antecedents and consequences of consumer switching intention in Ghana telecoms service context. They submited that switching intentions were found to negatively influence loyalty.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…By using Analyses of Moment Structure (AMOS), feature estimates were obtained using maximum likelihood, and confidence intervals were calculated by bootstrapping. Nimako and Nyame (2015) reviewed a theoretical model in consumer switching behaviour (CSB), and their study reveals that at least 10 theoretical models of CSB already exist. The gap on the existing CSB model is that they do not address issues related to computing research area.…”
Section: Practical Knowledge Gapsmentioning
confidence: 99%